1989
DOI: 10.1177/37.5.2649557
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of antibody against human liver guanase by immunoblotting and immunohistochemical staining of human liver guanase by a direct labeling antibody-enzyme method.

Abstract: Human liver guanase was purified and a specific antibody against it was raised in rabbits. The antiserum formed a single precipitin line with human liver extract, and also completely inhibited the activity of the liver enzyme. An immunoblotting study showed that the antibody bound specifically to one band of protein with guanase activity and not to other proteins. Therefore, we concluded that this antiserum against the liver enzyme was suitable for use in immunohistochemical demonstration of guanase. In tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…GAH catalyzes the hydrolytic deamination of guanine, yielding xanthine and ammonium, and is considered to be involved in a major pathway for producing uric acid (30). As consistent with our findings, GAH was shown to be abundant in brain, and its activity was detected in both nuclear and cytosolic fractions (31)(32)(33), although the biological significance has been largely unknown.…”
Section: Discussionsupporting
confidence: 78%
“…GAH catalyzes the hydrolytic deamination of guanine, yielding xanthine and ammonium, and is considered to be involved in a major pathway for producing uric acid (30). As consistent with our findings, GAH was shown to be abundant in brain, and its activity was detected in both nuclear and cytosolic fractions (31)(32)(33), although the biological significance has been largely unknown.…”
Section: Discussionsupporting
confidence: 78%
“…In a previous study (13), the immunohistochemical reaction was positive at the same sites as the histochemical reaction for guanase with DAB in human liver sections and was negative in control sections. Thus the distribution of the brown discoloration of oxidized DAB obtained by this method was in accordance with the specific location of guanase.…”
Section: Discussionmentioning
confidence: 99%
“…We used the purified enzyme to prepare antihuman liver guanase serum. Then we studied the distribution of guanase in human kidney by a previously reported histochemical staining method (7) and by the direct labelling antibody enzyme method (13). We also examined the guanase activity in nephron segments by a micromethod (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, histochemical and immunohistochemical analyses of human kidney and liver assigned cytoplasmic localisation [Ito et al, 1989;Kubo et al, 2006], which was also shown by differential centrifugation in rat and mouse brain cells [Kumar et al, 1972].…”
Section: ) Was Homologous To the Conserved Sequence Pgx[v/i] Dxh[t/mentioning
confidence: 98%